La comprensión de sí y el encuentro con el otro: reflexiones sobre educación y alteridad en la sociedad contemporánea - Norambuena-Paredes, Ignacio (2025)
The essay explores the relationship between self-understanding and alterity in the educational sphere, drawing on the philosophical perspective of Paul Ricoeur. It examines how dialogue and active listening serve as essential tools in shaping students’ critical thinking and identity. Additionally, it highlights the role of reading as a space for reflective mediation that facilitates encounters with different perspectives, challenging preconceived notions and broadening one’s understanding of the world. In the digital era, where algorithms reinforce the homogenization of thought, the essay underscores the need to reclaim alterity in education. It emphasizes the value of text as an «otherness» that engages the reader, fostering reflection and ethical development. Thus, education should not only focus on the transmission of knowledge but also on the formation of critical and open-minded individuals.